Analysis Of Defect Reduction Using The Six Sigma Method In A Fertilizer Factory In Gresik Regency - Pranata, Endru Jati; Santoso , Rahmat Agus (Jurnal Economic Resource, 2024)
This study analyzes efforts to reduce the defect rate at a fertilizer factory in Gresik Regency, a company that produces agricultural fertilizers, by implementing the Six Sigma method. The main problem faced by the company is the high level of product defects caused by human factors, methods, machines, and materials, which have an impact on fertilizer quality and production efficiency. This study uses a qualitative approach with the DMAIC (Define, Measure, Analyze, Improve, and Control) method to identify the main causes of defects and formulate improvement strategies. Data were collected through direct observation, interviews with the production and quality control teams, and analysis of documentation related to the level of product defects. The results of the study indicate that the main factors causing defects include lack of operator skills, inconsistency of production procedures, disruption to machines, and instability of raw material quality. By implementing the Six Sigma DMAIC method, the company can reduce the defect rate by improving workforce skills, standardizing work procedures, optimizing machine maintenance, and strict supervision of raw material quality. The implementation of this method is expected to improve the quality of fertilizer products and production efficiency at fertilizer factories in Gresik Regency